Thermal aspects of electrokinetic flow and capillary electrophoresis in microchannel network - Tang, Gongyue (2008)
Owing to numerous merits including improved resolution, increased throughput, reduced analysis time and decreased sample consumption, the microfluidic devices have found a wide spectrum of applications in the biomedical areas such as DNA sequencing, nucleic acid analysis, enzyme assays, immunoassays, etc. In microfluidic devices, electrokinetic transport, which in principle exploits two driving mechanisms - electrophoresis and electroosmosis, is used extensively to control liquid buffer flow and manipulate samples of nano/pico-liter volumes. It is known that the presence of Joule heating imposes limitations to the performance of electrokinetic transport. However, systematic investigations of the Joule heating and its effects on electroosmotic flow and electrokinetic mass transport based on the rigorous mathematical models still remain limited. In light of this, this dissertation provides a fundamental, systematic and in-depth exploration on the Joule heating and its effect on the electrokinetic transport in microfluidic systems.